STRATEGY OF GILL NET FISHING OPERATIONS FOR COASTAL FISHERIES MANAGEMENT IN BATANG REGENCY - Rochmat, Rochmat; Mudzakir, Abdul Kohar; Santoso, Agus; Sudarmo, Agnes Puspitasari (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2023)
Batang Regency is located on the North Coast of Central Java, with geographical coordinates between 6°51'46